Soy and breast cancer: focus on angiogenesis - Varinska, Lenka; Gal, Peter; Mojzisova, Gabriela; Mirossay, Ladislav; Mojzis, Jan (International journal of molecular sciences, 2015)
Epidemiological studies have revealed that high consumption of soy products is associated with low incidences of hormone-dependent cancers, including breast and prostate cancer. Soybeans contain large amounts of isoflavones, such as the genistein and daidzain. Previously, it has been demonstrated that genistein, one of the predominant soy isoflavones, can inhibit several steps involved in carcinogenesis. It is suggested that genistein possesses pleiotropic molecular mechanisms of action including inhibition of tyrosine kinases, DNA topoisomerase II, 5α-reductase, galectin-induced G2/M arrest, protein histidine kinase, and cyclin-dependent kinases, modulation of different signaling pathways associated with the growth of cancer cells (e.g., NF-κB, Akt, MAPK), etc. Moreover, genistein is also a potent inhibitor of angiogenesis. Uncontrolled angiogenesis is considered as a key step in cancer growth, invasion, and metastasis. Genistein was found to inhibit angiogenesis through regulation of multiple pathways, such as regulation of VEGF, MMPs, EGFR expressions and NF-κB, PI3-K/Akt, ERK1/2 signaling pathways, thereby causing strong antiangiogenic effects. This review focuses on the antiangiogenic properties of soy isoflavonoids and examines their possible underlying mechanisms.
Keywords: patologická angiogeneze; Animals; nádory prsu; Female; Glycine max; Genistein; breast cancer; ženské pohlaví; lidé; Breast; Angiogenesis Inhibitors; inhibitory angiogeneze; Isoflavones; prsy; Breast Neoplasms; soy; angiogenesis; signální transdukce; Signal Transduction; genistein; galectins; isoflavony; Neovascularization, Pathologic; zvířata; Humans